The Relationships between the Physical and Chemical Properties of Narrow Fractions Distilled From Mixed Kirkuk and Sharki-Baghdad Crude Oils - Abdul-Karim Mohammed, Abdul-Halim; G. Attiya, Hadi; Abdul Khaliq Khudair, Hayder (Iraqi Journal of Chemical and Petroleum Engineering, 2008)
Mixed Kirkuk and Sharki-Baghdad crude oils were distilled into narrow fractions. The range of these narrow fractions were 10oC, starting from IBP to 350oC. The total distillates from mixed Kirkuk and Sharki-Baghdad crude oils were 58.25 vol % and 44.65 vol %, respectively.The hydrocarbons compositions (paraffin, naphthene, aromatic) in light fractions starting from IBP to 250oC were determined by using PONA analysis method. The results show that the paraffin content decreases with increasing mid percent boiling point of the fraction, while the naphthene, and aromatic increase with the increase of mid percent boiling point of mixed Kirkuk and Sharki-Baghdad crude oils. Three groups of empirical equations were developed for the prediction of hydrocarbons compositions (paraffin, naphthene, aromatic) based on physical properties (mid percent boiling point, specific gravity, and refractive index) of narrow fractions distilled from mixed Kirkuk and Sharki-Baghdad crude oils. The first group relates the mid percent boiling point with the specific gravity, the second group relates the mid percent boiling point with the refractive index, while the third group relates the specific gravity with the refractive index.